Developing Culture-Based English Instructional Materials for Grade VII of Junior High School Students - Wiwiek Afifah Afifah (English Language Teaching Educational Journal, 2018)
The research aims at developing culture-based English instructional materials (henceforth, CBEIM) for grade VII of Junior High School students and reveal its final product representation in terms of its effectiveness. The research design was a research and development. The procedure of product development consisted of conducting needs analysis, designing course grids, developing the first draft, implementing the final draft, and evaluating the final product. The product implementation consisted of the 1st tryout involving 4 students from Yogyakarta State Junior High School (henceforth, Y-SJHS) 10, the 2nd tryout involving 34 students from Y-SJHS 7, and there were 68 students involved in the 3rd tryout. They were from Y-SJHS 9 and Y-SJHS 10. The data were collected by using evaluation sheets, an English achievement test, questionnaire to measure students’ level of internalization and actualization toward culture values, and questionnaires for teachers’ responses. The data were analyzed by t-test using paired and independent sample with the gain score. The research finding reveals 1) based on the content expert validation, CBEIM was very good by the aspect of content, language, learning, culture, presentation, and graphical design, whereas based on the graphical design expert, CBEIM was good. 2) Having been implemented, the final product representation was proven to be effective. The students in the experiment classes got a higher improvement than those in the control classes. The statistical calculation of independent samples test with gain score of the English test from the two groups shows the t values of 2.931 with the p = 0.004 < 0.05, while the t-test for equality of means of culture values, t value reached 2.524 and its significance of 2-tailed reached p = 0.037 < 0.05, alpha value (α=0.05). Since the gain score is smaller than 0.05, CBEIM demonstrates that it can show a significant difference between the experiment and control classes in encouraging students to internalize and actualize the culture values.